PREVALENSI PENDERITA DEMAM BERDARAH DENGUE (DBD) DI RUMAH SAKIT PTPN II BANGKATAN KOTA BINJAI TAHUN 2017 - Helvia Gusvita (Jurnal Riset Hesti Medan, 2017)
Dangue Hemorrhagic Fever (DHF) is a disease caused by a dangue virus infection consisting of four types, Den-1, Den-2, Den-3, and Den-4 which are transmitted by the bite of infected Aedes Aegypti and Albopiktus mosquitoes by dangue virus from previous DHF sufferers. This research is a survey identifying the prevalence of Dangue Hemorrhagic Fever (DHF) patients admitted to PTPN II Departure Hospital in Binjai City for the 2017 period using secondary data from medical records. The data collection tool in this study using observation tables grouped by age, gender, and length of treatment then analyzed data. From the results of this study, it can be seen that the prevalence of Dengue Hemorrhagic Fever (DHF) in PTPN II Departure Hospital in Binjai City The 2017 period is based on the age group of the majority of 6-10 years as many as 14 (35%), based on the sex of 23 women patients (57.5%), based on the length of stay in the majority of 7-14 days as many as 17 people (42.5%).Keywords: Prevalence of  Dengue Dengue Hemorrhagic, Dengue Dengue Hemorrhagic